Structural features of correlations in lines with the naturally colored fiber in the trait-specific collection - L. P. Podolnaya; R. K. Tuz; M. Sh. Asfandiiarova; T. P. Rybakova; N. A. Khodjaeva (Труды по прикладной ботанике, генетике и селекции)
Background. The overwhelming majority of commercial cotton cultivars have white fiber. Production of fabrics from such fiber has some disadvantages, therefore an increasing number of genotypes of cotton with the naturally colored fiber is being created around the world in the last decades. An investigation of correlations between different traits makes it possible to reveal the degree of influence of fiber color on structural and agronomic characters, and determine the possibility of creating varieties with naturally colored fiber for profitable cultivation in the north of the Astrakhan Province.Material and methods. Fourteen early lines of upland cotton (Gossypium hirsutum L.) from the trait-specific collection, which have naturally colored fiber, were studied in the north of the Astrakhan Province at the Caspian Research Institute of Arid Agriculture (CRIAA). The study employed the techniques developed at VIR and took into account productivity elements and agronomic traits. The lines were created at the Prikumskaya Experiment and Breeding Station of the Stavropol Agricultural Research Institute (Budennovsk) and CRIAA on the basis of hybrids between Turkmen varieties with brown and green fiber and accessions of early white fiber cotton from Albania and Italy. Two lines had beige fiber, 6 light brown, and 6 green. Microsoft Excel 10 was used in the work.Results and Discussion. The analysis of genotypic correlations showed that due to the insufficiency of the total effective temperatures in 2013, no significant links of colored fiber with other signs were discovered. All the correlations were typical for cotton plants. In the more favorable conditions of 2014, the variability of quantitative traits increased and the correlations that were absent in the previous year were revealed. The negative correlation of fiber color with the first generative branch height (r = -0.53), and positive with the fiber yield (r = 0.57) indicate that the lines with brown fiber have a lower height of fruiting branches development (and potentially a shorter growing season) and a larger yield of fiber. By their characteristics, they approach the industrial white fiber cultivars. These results show that the creation of a cultivar with brown fiber in the near future in Russia is quite possible.